2011
DOI: 10.1097/mpg.0b013e31821de3fc
|View full text |Cite
|
Sign up to set email alerts
|

Amerindian mtDNA Haplogroups and Celiac Disease Risk HLA Haplotypes in Mixed‐blood Latin American Patients

Abstract: mtDNA haplogroups A/B/C/D were frequently found in celiac patients and controls, but no relations appeared between haplogroups, haplotypes, and clinical presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Abdominal pain was a main symptom in the 32 overweight patients detected, concurring with reports by Reilly [24] and Venkatasubramani [25]. Agreeing with previous local studies [10], a high percentage of patients (89%) exhibited intense histological damage in the small intestinal mucosa at diagnosis. Previous studies in Chile show that the frequency and distribution of Human Leucocyte Antigen (HLA) -DQ2 and -DQ8 differ from those reported in Europe [26], HLA-DQB1*0301 -HLA-DQA1*302 being more frequent, but we have no data suggesting that the clinical presentation of the disease may be influenced by these genetic differences.…”
Section: Clinical Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…Abdominal pain was a main symptom in the 32 overweight patients detected, concurring with reports by Reilly [24] and Venkatasubramani [25]. Agreeing with previous local studies [10], a high percentage of patients (89%) exhibited intense histological damage in the small intestinal mucosa at diagnosis. Previous studies in Chile show that the frequency and distribution of Human Leucocyte Antigen (HLA) -DQ2 and -DQ8 differ from those reported in Europe [26], HLA-DQB1*0301 -HLA-DQA1*302 being more frequent, but we have no data suggesting that the clinical presentation of the disease may be influenced by these genetic differences.…”
Section: Clinical Characteristicssupporting
confidence: 89%
“…Patients were diagnosed and followed in four main public pediatric hospitals in Santiago, Chile. CD has been assessed and described in patients of these hospitals in previous studies [8][9][10][11][12], providing insight about previous local conditions. Inclusion criteria were: (1) diagnosis based on at least one antibody measured [anti endomysium (EMA) and/or antitransglutaminase 2 (TTG) plus a duodenal histological lesion on endoscopic biopsies characterized by epithelial lymphocytosis and variable degrees of deepening of crypts and flattening of villi (Marsh 2 or more) [13]; (2) that weight and height data was available in at least two checkups within the first 12 months of GFD.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of food support, consisting mainly of wheat, may have played a role in this outcome. Similar to native populations in Brazil and Chile (17), our study showed that only 3% of subjects had the HLA DQ2 alleles (prevalent in European populations), while 48% had the DQ8. This contrasts with the increased HLA-DQ2 allele frequency detected in Asia with high CD prevalence, as demonstrated in several recent studies (17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 72%
“…As all of the aforementioned studies are European, we can assume an adequate validity when extrapolating these results in Europe and countries with predominantly European ancestors. In this sense, those studies showing higher frequencies of HLA-DQ2 and DQ8 negative CD patients (up to 9%) have been performed in Latin-American populations (25,26). The absence of HLA-DQ2 and DQ8 should be, therefore, carefully interpreted in non-Caucasian populations in terms of CD screening.…”
Section: Discussionmentioning
confidence: 99%